PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA DAN ETOS KERJA TERHADAP KINERJA PEGAWAI - Mita Julia Herawati; Siti Nur Qomariyah; Muhyiddin Arifin (JoEMS (Journal of Education and Management Studies), 2020)
An institution / agency can not be separated from the increase in superior and quality human resources for it must be managed properly in order to achieve the performance expected by an institution / agency. Human resources are very important role in an agency / government agency. This study aims to determine the effect of organizational culture, work discipline and work ethic on the performance of hospital employees dr. Moedjito Dwidjosiswojo Jombang. This type of research uses correlational. The population of this study was 116 employees. The sample studied was 90 respondents selected. The sampling technique uses probability sampling technique with Proportion Stratified Random Sampling method. The analytical method used is multiple regression analysis. The results of this study indicate that partially and simultaneously organizational culture, work discipline and work ethic significantly influence the performance of hospital employees dr. Moedjito Dwidjosiswojo Jombang.